Approaching a gender neutral PE-culture? An exploration of the phase of a divergent PE-culture. Issue 5 (27th May 2016) - Lundvall, Suzanne
Abstract: The aim of this study is to explore the phase of the divergent physical education (PE) culture in Sweden through the enactment of gender and how boundaries are formed and defended by symbolic mediating status and monopolization of resources. The study departures from a literature review with an inductive approach. Inspired by the method of critical incidents technique specific events have been studied to explore the longitudinal phase and the enactment of gender. Five critical incidents demonstrates how difference and similarity were created, maintained and contested, but also how the dismantling of gender differences came to be enacted and socially configured in space and time. The findings of the study point to a slow-but-still ongoing phase of dissolving symbolic and social boundaries. Going for a gender-neutral PE culture in the future seems to require our ability to both be gender sensitive and gender bend in order to transgress traditional gender order.